DNA G-quadruplex and its potential as anticancer drug target - Buket, ONEL (Sci China Chem, 2014)
G-quadruplex secondary structures are four-stranded globular nucleic acid structures form in the specific DNA and RNA G-rich sequences with biological significance such as human telomeres, oncogene-promoter regions, replication initiation sites, and 5′ and 3′-untranslated (UTR) regions. The non-canonical G-quadruplex secondary structures can readily form under physiologically relevant ionic conditions and are considered to be new molecular target for cancer therapeutics. This review discusses the essential progress in our lab related to the structures and functions of biologically relevant DNA G-quadruplexes in human gene promoters and telomeres, and the opportunities presented for the development of G-quadruplex-targeted small- molecule drugs.